The little elves seeking the beautiful world - Warner, Lucy Hamilton; Bardwell, George Willis, 1868-1937 (Salt Lake City, UT : Project Gutenberg, 2023)
"The Little Elves Seeking the Beautiful World: A Book for Children" by Lucy Hamilton Warner is a charming children$1 (Bs story written in the late 19th century. The book narrates the whimsical journey of four little elves as they embark on a quest to discover the beautiful world, seeking adventures beyond their homeland. It is an enchanting tale filled with elements of fantasy, exploration, and the underlying message about the values of home and contentment. In this delightful narrative, Queen Wishtah sends her loyal elves$1 (BSpider Eyes, Chip Wing, Pointed Toes, and Dusty Cap$1 (Bto find a suitable location for her new palace in a warmer land. Along their journey, they encounter various creatures, including a toad, glowworms, and a grasshopper, each providing guidance or challenges. Despite the many obstacles and moments of temptation to stray from their mission, the elves' determination persists. Ultimately, they learn that the beautiful world they sought exists not in distant places but within their own loving home, emphasizing the story's heartwarming message about the beauty of one's own surroundings and the importance of family and friendship. (This is an automatically generated summary.)s
Release date is 2023-02-20
Charlene Taylor and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive/American Libraries.)
Keywords: Fantasy literature; Animals -- Juvenile fiction; Conduct of life -- Juvenile fiction; Adventure stories; Voyages and travels -- Juvenile fiction; Youth -- Conduct of life -- Juvenile fiction; Queens -- Juvenile fiction; Happiness -- Juvenile fiction; Elves -- Juvenile fiction; Spiders -- Juvenile fiction